SnO2-based modified ceramic membrane as well as preparation method and application thereof

By preparing SnO2-based modified ceramic film on the ceramic film, using ultrasonic spraying method and dopants, the problem of removing low molecular weight pollutants and poor conducting film performance in traditional technology is solved, and efficient and stable wastewater treatment is achieved.

CN119455681APending Publication Date: 2025-02-18ORDOS SHENGYUAN WATER GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411570249.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional MF/UF filtration technology is difficult to effectively remove low molecular weight pollutants, and the performance of conductive organic membranes is poor, which limits the combination of electrochemical and membrane filtration technology.

Method used

Using SnO2-based modified ceramic film, prepared by ultrasonic spraying method, metal dopants such as Sb, Co, Ni, La, Mn, Al or Zn, and non-metal dopants such as F or N are added to form high conductivity and stability and electrocatalytic active membranes.

Benefits of technology

The SnO2-based modified ceramic membrane with high electrochemical stability, low cost and simple process can effectively remove organic pollutants and dirt on the membrane surface, significantly improving the efficiency of sewage treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455681A_ABST
    Figure CN119455681A_ABST
Patent Text Reader

Abstract

The invention provides a SnO2-based modified ceramic membrane as well as a preparation method and application thereof, and belongs to the technical field of sewage treatment. According to the invention, a Sn source, a metal dopant and a non-metal dopant are taken as raw materials, an ultrasonic spraying method is adopted, a precursor solution generates nano fog drops under the excitation of ultrasonic waves, the nano fog drops uniformly coat the surface of a ceramic membrane and are fully combined with the surface of the ceramic membrane; the metal-nonmetal doped tin-based conductive layer is stably coated on the surface of the ceramic membrane, so that the SnO2-based modified ceramic membrane with high conductivity and high electrocatalytic activity is obtained. According to the preparation method, the raw materials are cheap and easy to obtain, and the adopted ultrasonic spraying method and calcination treatment means are simple and convenient in process, low in cost and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sewage treatment, and in particular to a SnO 2 Base modified ceramic membrane and its preparation method and application. Background Art

[0002] In recent years, the application scale of ceramic membranes in the field of water treatment has continued to grow due to their excellent mechanical strength, thermal stability, chemical stability, anti-fouling and filtration separation performance. During the membrane cleaning process, ceramic membranes can also withstand higher intensity cleaning agent conditions, and simple physical backwashing can remove most of the pollutants on the surface of the ceramic membrane. The advantages of low-pressure membrane filtration include high-quality effluent, good pathogen removal, small footprint and relatively low life cycle cost. However, traditional MF / UF filtration still faces severe challenges and cannot eliminate low molecular weight pollutants (e.g., toxic and / or difficult to degrade organic micropollutants), which may be deposited on / inside the membrane matrix, causing loss of membrane flux, or no interception effect, resulting in small molecular pollutants still present in the effluent. In addition, due to the interception of large molecular organic matter and Ca 2+ Mg 2+ The membrane pore blockage and membrane pollution caused by the formation of dense deposition layers by ion scaling are also a major bottleneck problem in the application of membrane separation technology. Therefore, the integration with other mature technologies is of great significance for low-pressure membrane filtration to alleviate the environmental problems caused by the low removal efficiency of low molecular weight (or small particle size) pollutants and inhibit the formation of scale layers on the membrane surface of large molecular weight (or large particle size) pollutants.

[0003] At present, in engineering applications, chemical softening pretreatment, physical backwashing and chemical cleaning are basically used to slow down the flux decline in the membrane separation process, which increases the cost of softening agents and chemical cleaning agents and the irreversible damage to the membrane surface during chemical cleaning. Therefore, on the basis of clarifying the mechanism of the ceramic membrane fouling process, developing technical processes based on the advantages of ceramic membrane separation technology and slowing down the membrane fouling process is an effective way to solve water source pollution. Among the derivative processes of membrane separation technology, electric field assisted membrane fouling control is an innovative technology that can effectively slow down membrane fouling during membrane application. By using the membrane voltage applied by the DC power supply and the charge of potential pollutants in the wastewater, the transformation and migration of pollutants can be affected through electrochemical degradation and electrostatic adsorption / repulsion, thereby effectively reducing pollution. In addition, electrochemical oxidation is a very promising green treatment technology. Under the action of an external electric field, water molecules are oxidized to hydroxyl radicals (·OH) with strong oxidizing properties at the anode interface, which can oxidize and degrade organic pollutants in water. If the anode is made of materials such as iron, H +It reacts with iron to generate hydrogen gas, which increases the pH of water. However, the single electrochemical method has high energy consumption, and the reaction mainly occurs on the electrode surface, the interface reaction efficiency is low, and the mass transfer effect from the liquid phase to the solid phase electrode is poor. Therefore, researchers have tried to combine the two technologies of electrochemistry and membrane filtration, but most of the conductive membranes are organic membranes. The disadvantages of conductive organic membranes are that the hydrophilicity, membrane mechanical strength, anti-pollution, chemical stability and other properties are poor, which limits its development potential. Conductive ceramic membranes came into being, which organically combined the technical advantages of electrochemical oxidation and ceramic membrane filtration. The surface-modified conductive materials mainly include titanium dioxide, graphene, carbon nanotubes, etc., which lack sufficient and lasting conductivity. In addition, the conductive membrane modified with carbon materials (such as CNTs and GO) has the problem of low oxidation potential, which will lead to side reactions and affect the self-cleaning efficiency. Therefore, the application and promotion of the "electrolysis + membrane filtration" process is greatly limited, and it is urgent to develop conductive ceramic membrane materials with simple preparation process, low cost, high electrochemical stability and good electrocatalytic activity. Summary of the invention

[0004] The present invention aims to provide a SnO 2 Base modified ceramic membrane and preparation method and application thereof, the SnO 2 The modified ceramic membrane has high electrochemical stability, good electrocatalytic activity, simple preparation process and low cost.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a SnO 2 The method for preparing a modified ceramic membrane comprises the following steps:

[0007] A tin source, an alcohol solvent, a non-metallic dopant, a metal dopant and an acid solution are mixed to obtain a precursor solution;

[0008] The precursor liquid is intermittently sprayed on the surface of the ceramic membrane substrate by an ultrasonic spray method to obtain a composite ceramic membrane;

[0009] The obtained composite ceramic membrane is calcined to obtain SnO 2 Base modified ceramic membrane;

[0010] The metal dopant doped with metal elements includes Sb, Co, Ni, La, Mn, Al or Zn; the non-metal dopant doped with elements includes F or N.

[0011] Preferably, the tin source comprises SnCl 2 or SnCl 4 ; The alcohol solvent includes ethanol, methanol or ethylene glycol

[0012] Preferably, the non-metallic dopant comprises NH4 F or urea; the molar ratio of the doping element in the non-metallic dopant to Sn in the tin source is 0.5 to 2:1.

[0013] Preferably, the metal dopant comprises SbCl 3 、CoCl 2 、NiCl 2 、LaCl 3 、MnCl 2 、AlCl 3 or ZnCl 2 ; The molar amount of the doped metal element in the metal dopant is 1 to 12% of the molar amount of the Sn element in the tin source.

[0014] Preferably, the acid solution comprises concentrated hydrochloric acid, the mass concentration of the concentrated hydrochloric acid is 37%, the amount of the acid solution added relative to the alcohol solvent is 100 mL / L; and the mixing time is 30 to 180 min.

[0015] Preferably, the material of the ceramic membrane substrate includes Al 2 O 3 Or SiC; before the spraying, the ceramic membrane substrate is preheated for 1 to 3 hours and the temperature is raised to 350 to 500°C.

[0016] Preferably, the intermittent spraying conditions include: a spraying flow rate of 0.5 to 3 mL / min, 1 min per spray, and an intermittent time of 5 to 20 min; based on the ceramic membrane substrate, the spraying volume is 0.5 to 10 mL / cm 2 ;

[0017] The calcination temperature is 500-800° C. and the calcination time is 120-240 minutes.

[0018] The present invention provides SnO prepared by the preparation method described in the above technical solution 2 Modified ceramic membrane.

[0019] The present invention provides the SnO 2 The application of modified ceramic membrane in sewage treatment uses cross-flow electrochemical coupled membrane separation device for sewage treatment.

[0020] Preferably, the cross-flow electrochemical coupled membrane separation device comprises a raw water tank 1, a diaphragm pump 2, a power supply 3, an electrolysis-filtration reactor 4, a water production tank 5, a reflux water regulating valve 8 and a water production regulating valve 9, wherein the raw water tank 1, the diaphragm pump 2, the electrolysis-filtration reactor 4 and the water production tank 5 are connected in sequence; the power supply 3 is connected to the electrolysis-filtration reactor 4; a conductive ceramic membrane 6 and a cathode 7 are arranged in the electrolysis-filtration reactor 4; the reflux water regulating valve 8 is arranged in the pipeline between the electrolysis-filtration reactor 4 and the raw water tank 1, and the water production regulating valve 9 is arranged in the pipeline between the electrolysis-filtration reactor 4 and the water production tank 5; the conductive ceramic membrane 6 is the SnO 2 Base modified ceramic membrane; the SnO 2 The modified ceramic membrane was used as the anode.

[0021] The present invention provides a SnO 2 The invention discloses a method for preparing a modified ceramic membrane. The invention uses Sn source, metal dopant and non-metal dopant as raw materials, adopts ultrasonic spraying method, and produces nano-droplets of precursor liquid under ultrasonic excitation, which are uniformly coated on the surface of ceramic membrane and fully combined with the surface of ceramic membrane. Then, the metal-non-metal doped tin-based conductive layer is stably coated on the surface of ceramic membrane through calcination and pyrolysis treatment, thereby improving the stability of ceramic membrane. In addition, the doping sites of metal and non-metal are different, which can simultaneously improve SnO 2 The conductivity of - Replaced O 2- (Formula (1)), which adds more free electrons to the conduction band, Sb 5+ and Sn 4+ The substitution reaction between (formula (2)) will also generate free electrons, which improves the conductivity of the load layer and reduces the charge transfer resistance. In addition, the structure of the high-valent oxide crystal ensures that it will not corrode due to oxidation when used as an anode, thereby improving the stability of the electrode. Therefore, the present invention can obtain SnO with high conductivity, high stability and high electrocatalytic activity. 2 Modified ceramic membrane.

[0022]

[0023] The preparation method of the invention has cheap and easily available raw materials, adopts the ultrasonic spray method and calcination treatment means, has simple process and low cost, and is suitable for large-scale production.

[0024] The present invention uses the SnO 2The modified ceramic membrane is used as both anode and separation membrane in the treatment of organic wastewater. The presence of the metal-nonmetal doped tin-based conductive layer can play an electrocatalytic role. In the application process, a cross-flow electrochemical coupling membrane separation device is used, with a conductive ceramic membrane as the anode and Al (or Fe) as the cathode, and the membrane filtration process is carried out synchronously during the power-on process. 2 The conductive layer in the modified ceramic membrane can effectively remove organic pollutants and organic fouling on the membrane surface under the action of voltage-induced electro-oxidation, in-situ electrogenerated ROS, electrostatic action, and electrogenerated bubbles. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The Sb-F co-doped SnO prepared in Example 1 2 SEM images of modified ceramic membranes, where (a) is the cross section of the modified ceramic membrane and (b) is the surface of the modified layer;

[0026] Figure 2 The Sb-F co-doped SnO prepared in Example 1 2 Pore ​​volume and pore size diagram of modified ceramic membrane;

[0027] Figure 3 The Sb-F co-doped SnO prepared in Example 1 2 XRD pattern of the modified ceramic membrane;

[0028] Figure 4 The Sb-F co-doped SnO prepared in Example 1 2 XPS graph of the modified ceramic membrane;

[0029] Figure 5 Sb-F co-doped SnO prepared in Example 1 2 The volt-ampere characteristic curve of the modified ceramic membrane.

[0030] Figure 6 The Sb-F co-doped SnO prepared in Example 1 2 Electrochemical impedance spectroscopy of the modified ceramic membrane;

[0031] Figure 7 is a SEM image of the commercial porous alumina ceramic membrane in Comparative Example 1;

[0032] Figure 8 The electrochemical coupled membrane separation treatment device used for testing in the embodiment (wherein: 1-raw water tank; 2-diaphragm pump; 3-power supply; 4-electrolysis-filtration reactor; 5-water production tank; 6-conductive ceramic membrane; 7-cathode; 8-return water regulating valve; 9-water production regulating valve);

[0033] Fig. 9The water flux variation curve of the modified ceramic membrane in Example 1 and the commercial porous alumina ceramic membrane in Comparative Example 1 during the sewage treatment process;

[0034] Fig.10 This is the EPR spectrum of the modified ceramic membrane in wastewater in Example 1. DETAILED DESCRIPTION

[0035] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0036] The present invention provides a SnO 2 The method for preparing a modified ceramic membrane comprises the following steps:

[0037] A tin source, an alcohol solvent, a non-metallic dopant, a metal dopant and an acid solution are mixed to obtain a precursor solution;

[0038] The precursor liquid is intermittently sprayed on the surface of the ceramic membrane substrate by an ultrasonic spray method to obtain a composite ceramic membrane;

[0039] The obtained composite ceramic membrane is calcined to obtain SnO 2 Base modified ceramic membrane;

[0040] The metal dopant doped with metal elements includes Sb, Co, Ni, La, Mn, Al or Zn; the non-metal dopant doped with elements includes F or N.

[0041] The invention mixes a tin source, an alcohol solvent, a non-metallic dopant, a metal dopant and an acid solution to obtain a precursor solution.

[0042] In the present invention, the tin source preferably includes SnCl 2 or SnCl 4 ; The alcohol solvent preferably includes ethanol, methanol or ethylene glycol.

[0043] In the present invention, the concentration of the tin source in the alcohol solvent is preferably 0.1 to 0.6 mol / L (calculated as the concentration of Sn ions), and more preferably 0.4 mol / L.

[0044] In the present invention, the metal dopant in the metal dopant includes Sb, Co, Ni, La, Mn, Al or Zn; the metal dopant preferably includes SbCl 3 、CoCl 2 、NiCl 2 、LaCl 3 、MnCl 2 、AlCl 3 or ZnCl 2 .

[0045] In the present invention, the molar amount of the doped metal element in the metal dopant is preferably 1 to 12% of the molar amount of the Sn element in the tin source, more preferably 8 to 10%, and further preferably 9%.

[0046] In the present invention, the doping element in the non-metallic dopant preferably includes F or N, and the non-metallic dopant is preferably NH 4 F or urea.

[0047] In the present invention, the molar ratio of the doping element in the non-metallic dopant to Sn in the tin source is 0.5 to 2:1, more preferably 0.8 to 1.5:1, and further preferably 1:1.

[0048] In the present invention, the acid solution preferably includes concentrated hydrochloric acid, the mass concentration of the concentrated hydrochloric acid is preferably 37%, the amount of the acid solution added relative to the alcohol solvent is preferably 100 mL / L; the mixing time is preferably 30 to 180 min, more preferably 60 min. The role of the acid solution in the present invention is to dissolve metal and non-metal components, avoid precipitation, make the precursor solution transparent, and realize the smooth progress of the subsequent spraying process.

[0049] The present invention preferably mixes the tin source with an alcohol solvent, adds a non-metallic dopant, then adds a metal dopant, and then adds an acid solution, and stirs and mixes to obtain a clear and transparent precursor solution.

[0050] After obtaining the precursor liquid, the present invention adopts an ultrasonic spray method to intermittently spray the precursor liquid onto the surface of the ceramic membrane substrate to obtain a composite ceramic membrane.

[0051] In the present invention, the material of the ceramic membrane substrate preferably includes Al 2 O 3 Or SiC. The present invention has no particular limitation on the source of the ceramic membrane substrate, and any commercially available product known in the art may be used.

[0052] In the present invention, before the spraying, the ceramic membrane substrate is preheated in the electric heating plate (100-450°C) of the UAM4000L-HT high-temperature ultrasonic spraying system for 1-3 hours, more preferably 2 hours, and the temperature is raised to 350-500°C, more preferably 450-480°C.

[0053] The present invention preferably uses a UAM4000L-HT high temperature ultrasonic spraying system to evenly spray the precursor liquid onto the surface of the ceramic membrane substrate. Since liquid spraying causes the substrate temperature to drop rapidly, intermittent spraying is used to avoid the temperature being too low to cause the load layer to produce crystal water, causing the load conductive layer membrane to have an uneven pore size distribution.

[0054] In the present invention, the intermittent spraying conditions preferably include: a spraying flow rate of 0.5 to 3 mL / min, each spraying for 1 min, an intermittent time of 5 to 20 min, a spraying flow rate of more preferably 1 to 2 mL / min, an intermittent time of more preferably 10 min, and a spraying amount of 0.5 to 10 mL / cm based on the ceramic membrane substrate. 2 , more preferably 5 mL / cm 2 .

[0055] In the process of spraying by ultrasonic spray method, oxide crystals are initially formed in the range of 400-500° C. provided by the high temperature ultrasonic spray system.

[0056] After obtaining the composite ceramic membrane, the present invention calcines the obtained composite ceramic membrane to obtain SnO 2 Modified ceramic membrane.

[0057] In the present invention, the calcination temperature is preferably 500-800°C, more preferably 600-700°C, the time is preferably 120-240 min, more preferably 180 min, and the atmosphere is air atmosphere; the heating rate to the calcination temperature is preferably 5°C / min.

[0058] During the calcination process, SnO 2 Defect generation, F- replaces O 2- (Formula (1)), which adds more free electrons to the conduction band, Sb 5+ and Sn 4+ The substitution reaction between them (Formula (2)) will also produce free electrons, thereby improving the conductivity of the load layer and reducing the charge transfer resistance.

[0059] After the calcination, the present invention preferably cools naturally to obtain SnO 2 Modified ceramic membrane.

[0060] The present invention provides SnO prepared by the preparation method described in the above technical solution 2 Modified ceramic membrane.

[0061] The present invention provides the SnO 2 The application of modified ceramic membrane in sewage treatment uses cross-flow electrochemical coupled membrane separation device for sewage treatment.

[0062] In the present invention, if Figure 8As shown, the cross-flow electrochemical coupling membrane separation device includes a raw water tank 1, a diaphragm pump 2, a power supply 3, an electrolysis-filtration reactor 4, a water production tank 5, a conductive ceramic membrane 6, a cathode 7, a reflux water regulating valve 8 and a water production regulating valve 9. The raw water tank 1, the diaphragm pump 2, the electrolysis-filtration reactor 4 and the water production tank 5 are connected in sequence; the power supply 3 is connected to the electrolysis-filtration reactor 4; the electrolysis-filtration reactor 4 is provided with a conductive ceramic membrane 6 and a cathode 7; the reflux water regulating valve 8 is provided in the pipeline between the electrolysis-filtration reactor 4 and the raw water tank 1, and the water production regulating valve 9 is provided in the pipeline between the electrolysis-filtration reactor 4 and the water production tank 5; the conductive ceramic membrane 6 is the SnO 2 Base modified ceramic membrane; the SnO 2 The modified ceramic membrane was used as the anode.

[0063] The present invention has no particular limitation on the process of assembling the conductive ceramic membrane 6 and cathode 7 into the electrolysis-filtration reactor 4. The conductive ceramic membrane 6 and cathode 7 can be installed in a conventional container to form the electrolysis-filtration reactor 4 in a manner well known in the art.

[0064] In the present invention, the cathode 7 is preferably a Fe electrode or an aluminum electrode.

[0065] The present invention has no special limitation on the specific structure and connection process of each component in the cross-flow electrochemical coupled membrane separation device, and corresponding component pipelines well known in the art can be used for connection.

[0066] In the cross-flow electrochemical coupled membrane separation device described in the present invention, the outlet water of the raw water tank 1 is connected to the diaphragm pump 2, and the wastewater flows to the electrolysis-filtration reactor 4 under the pressure of the diaphragm pump 2, and is filtered out from the conductive ceramic membrane and enters the water production tank 5 under pressure drive; the water flow in the middle of the electrolysis-filtration reactor 4 is controlled by adjusting the reflux water regulating valve 8 to control the water volume of the reflux water, and the reflux water flows from the electrolysis-filtration reactor 4 to the raw water tank 1.

[0067] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0068] Example 1

[0069] Weigh 7.5664 g (0.04 mol) SnCl 2 Dissolve in 100 mL of anhydrous ethanol (i.e., Sn ion concentration is 0.4 mol / L), add 1.48148 g (0.04 mol) NH 4 F (molar ratio F:Sn = 1) and 0.9124 g (0.004 mol) SbCl 3(the molar amount of Sb is 10% of Sn), then add 10 mL of concentrated hydrochloric acid with a mass concentration of 37% (i.e., 100 mL / L), stir at a speed of 600 rpm for 60 min, and obtain a clear and transparent precursor liquid;

[0070] The porous alumina ceramic membrane substrate (Anhui Tianling Technology Co., Ltd.; model: pore size 500nm, thickness 4mm, diameter 38mm) was preheated for 2h in the electric heating plate (400℃) of the UAM4000L-HT high-temperature ultrasonic spraying system, and the temperature was raised to 480℃. The precursor liquid was evenly and intermittently sprayed onto the surface of the ceramic membrane substrate using the UAM4000L-HT high-temperature ultrasonic spraying system. The spraying flow rate was 2mL / min for 1min, and the next spraying was paused for 10min. The spraying amount on the surface of the ceramic membrane substrate was 5mL / cm 2 After spraying 50 mL of the precursor solution in this intermittent manner, the ceramic film was quickly transferred to a muffle furnace, heated to 700 °C at a heating rate of 5 °C / min, calcined for 180 min, and cooled naturally to obtain Sb-F co-doped SnO 2 Modified ceramic membrane.

[0071] Example 2

[0072] Weigh 7.5664 g (0.04 mol) of SnCl 2 Dissolve in 100 mL of anhydrous ethanol (i.e., Sn ion concentration is 0.4 mol / L), add 0.74074 g (0.02 mol) of NH 4 F (molar ratio F: Sn = 0.5), add 0.4027g (0.003mol) of MnCl 2 (the molar amount of Mn is 8% of Sn), then add 10 mL of concentrated hydrochloric acid with a mass concentration of 37% (i.e., 100 mL / L), stir at a speed of 600 rpm for 60 min, and obtain a clear and transparent precursor liquid;

[0073] The porous alumina ceramic membrane substrate (same as in Example 1) was preheated for 2 h in the electric heating plate (400 ° C) of the UAM4000L-HT high-temperature ultrasonic spraying system, and the temperature was raised to 480 ° C. The precursor liquid was evenly and intermittently sprayed onto the surface of the ceramic membrane using the UAM4000L-HT high-temperature ultrasonic spraying system. The spraying flow rate was 2 mL / min for 1 min, and the next spraying was paused for 10 min. The spraying amount on the surface of the ceramic membrane substrate was 5 mL / cm 2 After spraying 40 mL of the precursor solution in this intermittent manner, the ceramic film was quickly transferred to a muffle furnace, heated to 700 °C at a heating rate of 5 °C / min, calcined for 180 min, and cooled naturally to obtain Mn-F co-doped SnO 2 Modified ceramic membrane.

[0074] Example 3

[0075] Weigh 7.5664 g (0.04 mol) of SnCl 2 Dissolve in 100 mL of anhydrous ethanol (i.e., Sn ion concentration is 0.4 mol / L), add 2.4024 g (0.04 mol) of urea CO (NH 2 ) 2 (molar ratio N:Sn=1), add 0.8212g (0.0036mol) of SbCl 3 (the molar amount of Sb is 9% of Sn), then add 10 mL of concentrated hydrochloric acid with a mass concentration of 37% (i.e., 100 mL / L), stir at a speed of 600 rpm for 60 min, and obtain a clear and transparent precursor liquid;

[0076] The porous alumina ceramic membrane substrate (same as in Example 1) was preheated for 2 h in the electric heating plate (400 ° C) of the UAM4000L-HT high-temperature ultrasonic spraying system, and the temperature was raised to 480 ° C. The precursor liquid was evenly and intermittently sprayed onto the surface of the ceramic membrane using the UAM4000L-HT high-temperature ultrasonic spraying system. The spraying flow rate was 2 mL / min for 1 min, and the next spraying was paused for 10 min. The spraying amount on the surface of the ceramic membrane substrate was 5 mL / cm 2 After spraying 50 mL of the precursor solution in this intermittent manner, the ceramic film was quickly transferred to a muffle furnace, heated to 700 °C at a heating rate of 5 °C / min, calcined for 180 min, and cooled naturally to obtain Sb-N co-doped SnO 2 Modified ceramic membrane.

[0077] Comparative Example 1

[0078] Commercial porous alumina ceramic membrane (Anhui Tianling Technology Co., Ltd.; model: pore size 500 nm, thickness 4 mm, diameter 38 mm).

[0079] Comparative Example 2

[0080] Weigh 7.5664g SnCl 2 Dissolve in 100 mL of anhydrous ethanol (i.e., Sn ion concentration is 0.4 mol / L), then add 10 mL of concentrated hydrochloric acid with a mass concentration of 37% (i.e., 100 mL / L), and stir at 600 rpm for 60 min to obtain a clear and transparent precursor liquid;

[0081] The porous alumina ceramic membrane substrate (same as in Example 1) was preheated for 2 h in the electric heating plate (400 ° C) of the UAM4000L-HT high-temperature ultrasonic spraying system, and the temperature was raised to 480 ° C. The precursor liquid was evenly and intermittently sprayed onto the surface of the ceramic membrane using the UAM4000L-HT high-temperature ultrasonic spraying system. The spraying flow rate was 2 mL / min for 1 min, and the next spraying was paused for 10 min. The spraying amount on the surface of the ceramic membrane substrate was 5 mL / cm 2 After spraying 50 mL of the precursor solution in this intermittent manner, the ceramic membrane was quickly transferred to a muffle furnace and heated to 700 °C at a heating rate of 5 °C / min for 180 min. After cooling naturally, undoped SnO 2 Modified ceramic membrane.

[0082] Characterization and performance testing

[0083] Figure 1 The Sb-F co-doped SnO prepared in Example 1 2 SEM images of modified ceramic membranes ((a) is the cross section of the modified ceramic membrane, (b) is the surface of the modified layer), Figure 2 The Sb-F co-doped SnO prepared in Example 1 2 The pore volume and pore size distribution of the modified ceramic membrane. Figure 3 The Sb-F co-doped SnO prepared in Example 1 2 XRD pattern of modified ceramic membrane. Figure 4 The Sb-F co-doped SnO prepared in Example 1 2 XPS graph of modified ceramic membrane Figure 1 , 3 It can be clearly seen from Figures 4 and 5 that there is an obvious coating on the surface of the modified conductive ceramic film material, and the coating is Sb and F co-doped SnO 2 .from Figure 2 It can be seen that a porous ceramic membrane with an average pore size of 218.5 nm is formed.

[0084] Figure 5 The Sb-F co-doped SnO prepared in Example 1 2 The volt-ampere characteristic curve of the modified ceramic membrane. Figure 6 The Sb-F co-doped SnO prepared in Example 1 2 Electrochemical impedance spectroscopy of the modified ceramic membrane. Figure 5 , 6 It can be seen that the modified conductive ceramic membrane material has excellent electrocatalytic properties.

[0085] The resistance analysis data of the ceramic films in Examples 1 to 3 and Comparative Examples 1 to 2 were tested using a square probe resistance measurement method. The results are shown in Table 1.

[0086] Table 1 Conductive properties of ceramic films in Examples 1 to 3 and Comparative Examples 1 to 2

[0087]

[0088] As shown in Table 1, the modified conductive ceramic membrane material has excellent conductivity, and the modified ceramic membranes in Examples 1 to 3 have significantly better conductivity than commercial porous alumina ceramic membranes and undoped SnO 2 Modified ceramic membrane.

[0089] Figure 7 This is the SEM image of the commercial porous alumina ceramic membrane in Comparative Example 1. It can be seen that the unmodified ceramic membrane does not have a supported conductive layer.

[0090] Test Case

[0091] The SnO prepared in Examples 1 to 3 2 The modified ceramic membrane and the commercial porous alumina ceramic membrane in Comparative Example 1 and the undoped SnO 2 The modified ceramic membrane was tested for performance in organic wastewater, which contained 100 mg / L of protein pollutants and 50 mg / L of humic acid pollutants:

[0092] The commercial porous alumina ceramic membrane in Comparative Example 1 is used as a separation membrane, and the sewage treatment reaction device is as follows Figure 8 As shown. The initial membrane flux was controlled to be 200LMH and the electrolyte was 0mM Na 2 SO 4 , current density is 0mA / cm 2 , for wastewater treatment.

[0093] The undoped SnO in Comparative Example 2 2 The modified ceramic membrane and the modified ceramic membrane in Examples 1 to 3 are used as both anode and separation membrane, and the sewage treatment reaction device is as follows Figure 8 As shown. The initial membrane flux was controlled to be 200LMH and the electrolyte was 50mM Na 2 SO 4 , current density is 10mA / cm 2 At the same time, the commercial porous alumina ceramic membrane in Comparative Example 1 was used to treat wastewater with an initial membrane flux of 200LMH. The results are shown in Table 2.

[0094] Table 2 Removal effect of humic acid and protein pollutants in wastewater treatment by ceramic membranes in Examples 1 to 3 and Comparative Examples 1 to 2

[0095]

[0096] As shown in Table 2, the wastewater treatment efficiency of the modified ceramic membranes in Examples 1 to 3 after doping with metal and non-metal elements is significantly better than that of the commercial porous alumina ceramic membrane and the undoped SnO 2 Modified ceramic membrane. Therefore, compared with the commercial porous alumina ceramic membrane (simple membrane separation process), the electrochemical coupled membrane separation process of the present invention has better wastewater treatment efficiency.

[0097] Fig. 9 is a curve diagram of water flux variation of the modified ceramic membrane in Example 1 and the commercial porous alumina ceramic membrane in Comparative Example 1 during sewage treatment; Fig. 9 It can be seen that the modified ceramic membrane prepared in Example 1 exhibits excellent, stable water flux and high pollutant removal rate in the electrochemical coupled membrane separation reaction device, which is significantly better than the commercial porous alumina ceramic membrane.

[0098] Fig.10 is the EPR spectrum of the modified ceramic membrane in wastewater in Example 1; Fig.10 As shown, the modified conductive ceramic membrane exhibited excellent ROS generation ability.

[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a SnO2-based modified ceramic membrane, characterized in that: The following steps are involved: A tin source, an alcohol solvent, a non-metallic dopant, a metal dopant and an acid solution are mixed to obtain a precursor solution; The precursor liquid is intermittently sprayed on the surface of the ceramic membrane substrate by an ultrasonic spray method to obtain a composite ceramic membrane; The obtained composite ceramic membrane is calcined to obtain a SnO2-based modified ceramic membrane; The metal dopant doped with metal elements includes Sb, Co, Ni, La, Mn, Al or Zn; the non-metal dopant doped with elements includes F or N.

2. The preparation method according to claim 1, characterized in that: The tin source includes SnCl2 or SnCl4; the alcohol solvent includes ethanol, methanol or ethylene glycol.

3. The preparation method according to claim 1 or 2, characterized in that: The non-metallic dopant includes NH4F or urea; the molar ratio of the doping element in the non-metallic dopant to Sn in the tin source is 0.5 to 2:

1.

4. The preparation method according to claim 1 or 2, characterized in that: The metal dopant includes SbCl3, CoCl2, NiCl2, LaCl3, MnCl2, AlCl3 or ZnCl2; the molar amount of the doped metal element in the metal dopant is 1-12% of the molar amount of the Sn element in the tin source.

5. The preparation method according to claim 1, characterized in that: The acid solution includes concentrated hydrochloric acid, the mass concentration of the concentrated hydrochloric acid is 37%, and the addition amount of the acid solution relative to the alcohol solvent is 100 mL / L; the mixing time is 30 to 180 minutes.

6. The preparation method according to claim 1, characterized in that: The material of the ceramic membrane substrate includes Al2O3 or SiC; before the spraying, the ceramic membrane substrate is preheated for 1 to 3 hours and the temperature is raised to 350 to 500°C.

7. The preparation method according to claim 1, characterized in that: The intermittent spraying conditions include: a spraying flow rate of 0.5 to 3 mL / min, each spraying for 1 min, and an intermittent time of 5 to 20 min; based on the ceramic membrane substrate, the spraying volume is 0.5 to 10 mL / cm 2 ; The calcination temperature is 500-800° C. and the calcination time is 120-240 minutes.

8. The SnO2-based modified ceramic membrane prepared by the preparation method according to any one of claims 1 to 7.

9. The use of the SnO2-based modified ceramic membrane in sewage treatment according to claim 8, characterized in that: A cross-flow electrochemical coupled membrane separation device is used for wastewater treatment.

10. The use according to claim 9, characterized in that: The cross-flow electrochemical coupled membrane separation device comprises a raw water tank (1), a diaphragm pump (2), a power supply (3), an electrolysis-filtration reactor (4), a water production tank (5), a return water regulating valve (8) and a water production regulating valve (9), wherein the raw water tank (1), the diaphragm pump (2), the electrolysis-filtration reactor (4) and the water production tank (5) are connected in sequence; the power supply (3) is connected to the electrolysis-filtration reactor (4); a conductive ceramic membrane (6) and a cathode (7) are arranged in the electrolysis-filtration reactor (4); the return water regulating valve (8) is arranged in the pipeline between the electrolysis-filtration reactor (4) and the raw water tank (1), and the water production regulating valve (9) is arranged in the pipeline between the electrolysis-filtration reactor (4) and the water production tank (5); the conductive ceramic membrane (6) is the SnO2-based modified ceramic membrane described in claim 8; the SnO2-based modified ceramic membrane serves as an anode.